Determining Specific Window Period for Common Scab Disease Infection in Potato Tubers - Khatri, Bhim Bahadur; Tegg, R.S.; Brown, Philip H.; Wilson, C.R. (Journal of Nepal Agricultural Research Council, 2017)
A series of experiments was conducted under glasshouse and hydroponic conditions to determine the specific window period for common scab disease infection in potato tubers. The study was performed in a glasshouse system where separate tubers from the root zone were inoculated at different intervals during plant growth along with a novel hydroponic system to inoculate individual tubers at specific times of development growth allowing non-destructive observations of common scab symptoms developing. The window of tuber susceptibility to common scab disease infection was shown to vary with the season or conditions under which the plants were grown. Different internodes on tubers were found susceptible to infection at different times during tuber development. Basal internodes, which are the first sections of the tuber to expand, were susceptible to infection in the beginning of tuber development, whereas apical internodes only became susceptible later in tuber growth when the basal internodes were no longer susceptible. Journal of Nepal Agricultural Research Council Vol.3 2017: 19-26